(untitled) (Journal of Engineering, 2003)
An experimental investigation was made for the study of incompressible flow on a circular disc. It consists of two parts. The first was the determination of the pressure distribution of the front an! rear sides of three samples of dises with diameters 9.73,10.75 and 11.94cm and 3mm thickness.Th: dises were mounted normal to the flow direction. This part also included the determination of pressure distribution on the front and rear sides of an inclined dise of 10.75 cm diameter it inclination angles of 30, 60, 120, and 150 to the horizontal. The second part of the investigation was the determination of the drag coefficient on a circular disc 10.75 cm in diameter and 3 mm in thickness using two methods. The first using strain gages as sensitive elements. The strain readings were recorded and transformed into drag force by using a transformation system or by using the strain transformation equations. The second using a dial gage whereby the displacement was transformed into drag force. Drag determination was performed for normal and inclined disc. Inclination included 30,60 and 90 to the horizontal. Tests were made using a low speed wind tunnel, at low, medium and high velocities of 4.74, 8.316 and 10.35 m/s respectively. The experimental results compared well with theoretical predications and with available published data